Traditions of subversion and the subversion of tradition : cultural cristicism in Maidu clown performances. - Brigthman, Robert (American Antropological Association, 1999)
Reflecting changing disciplinary orientation, recent perspectives on non-Western ritual clowns have rejected earlier functionalist interpretations and foregrounded themes of criticism, deconstruction, and subversion. In this essay, I interpret a ritual clown performance formerly practiced by the Northwestern Maidu of California both as an objectification, by way of symbolic inversion, of valorized cultural forms and as a metasociological discourse on the relationship between egoistic dispositions and normative disciplinary constraints. The interpretation suggests that functional and subversive meanings and effects are fusional rather than opposing elements in such performances and that the Maidu clown is best understood in relation to quotidien modes of deviance and to the diverse social locations represented in his audience.